Microinversores baseados na topologia meia-ponte isolada alimentada em corrente - Andrade, António Manuel Santos Spencer (2018)
The Microinverter is an inverter sized to meet individual solar panels, usually consisting of two stages, one DC-DC stage and another CC-AC stage. For the first stage of the DC link microinverter, the isolated current-fed half-bridge converter was chosen because of its characteristics. Such as, lower number of components, simplicity of operation and higher voltage gain. The isolated current-fed half-bridge inverter was analyzed for the operating principle, static gain, voltage and current stresses, estimated losses and efficiency. To improve the performance of the isolated current-fed half-bridge converter, high voltage gain circuit techniques were evaluated and associated in the converter. In this way, four high step-up topologies are proposed and evaluated. In relation to CC-CA stage, the adopted converter is the buck with unfolding. The principle of operation, modeling and control, power losses estimation and design methodology of this converter are analyzed. In addition, a small modification in the circuit caused this topology to present an LCL filter, which is an attractive for systems connected in the grid tie. Finally, to validate the theoretical analyzes, five prototypes of 200 W are evaluated experimentally in the laboratory. The Microinverter based on isolated current-fed half-bridge with Cockcroft-Walton cell voltage multiplier presented better features among all DC-DC converters. On the other hand, the results of the CC-CA stage validated achieved the main objective of supplying power to the grid according to standard. Finally, the microinverter based on isolated current-fed half-bridge with Cockcroft-Walton cell and buck with unfolding is the one that achieved better performance.